2023
DOI: 10.1136/bmjdrc-2022-003046
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a multivariable genotype-informed gestational diabetes prediction algorithm for clinical use in the Mexican population: insights into susceptibility mechanisms

Abstract: IntroductionGestational diabetes mellitus (GDM) is underdiagnosed in Mexico. Early GDM risk stratification through prediction modeling is expected to improve preventative care. We developed a GDM risk assessment model that integrates both genetic and clinical variables.Research design and methodsData from pregnant Mexican women enrolled in the ‘Cuido mi Embarazo’ (CME) cohort were used for development (107 cases, 469 controls) and data from the ‘Mónica Pretelini Sáenz’ Maternal Perinatal Hospital (HMPMPS) coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Such methods are valid to predict GDM at any point of life. Their predictive power is moderate, e.g., with an NER of 0.531–0.552 [ 55 ] and an AUROC of 0.7694 [ 27 ]. Moreover, they are associated with long analysis times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such methods are valid to predict GDM at any point of life. Their predictive power is moderate, e.g., with an NER of 0.531–0.552 [ 55 ] and an AUROC of 0.7694 [ 27 ]. Moreover, they are associated with long analysis times.…”
Section: Discussionmentioning
confidence: 99%
“…This review revealed that many of the predictive models for this pregnancy disease derive from data acquired by instrumental techniques, such as liquid or gas chromatography coupled to mass spectrometry (LC-MS or GC-MS, respectively), nuclear magnetic resonance (NMR) spectroscopy, and polymerase chain reaction (PCR), among others [ 17 ]. More recently, new articles have been published in the context of GDM diagnosis based on the same techniques, i.e., LC-MS [ 18 , 19 , 20 , 21 ], GC-MS [ 22 ], NMR spectroscopy [ 23 ], and PCR [ 24 , 25 , 26 , 27 ]. Methods based on these techniques are very time consuming, as they require tedious sample preparation procedures or prolonged instrumental runs.…”
Section: Introductionmentioning
confidence: 99%
“…Their predictive power is moderate, e.g. with an accuracy of 0.531-0.552 [46] and an AUROC of 0.7694 [47]. Moreover, they are associated with long analysis times.…”
Section: Nir Data-based Prediction Has Advantages Over Other Instrume...mentioning
confidence: 99%
“…The PCR-RFLP protocol alone takes more than 2 hours. Likewise, the method of Zulueta et al [47] consists of genomic DNA extraction, and its analysis by iPLEX-PCR, using the MassARRAY system from Agena Bioscience. According to the manufacturer, the entire workflow for iPLEX MassARRAY PCR takes 8 hours [48].…”
Section: Nir Data-based Prediction Has Advantages Over Other Instrume...mentioning
confidence: 99%
“…Other studies using the data from the CME cohort study have been published previously. [19][20][21][22][23][24] We analyzed the 2-h 75-g OGTT results of 2056 Mexican pregnant women between 24 and 28 weeks of gestation, without a prior diagnosis of type 2 diabetes, from the CME cohort study.…”
Section: Study Populationmentioning
confidence: 99%